2016
DOI: 10.1016/j.jmii.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of mortality in patients with carbapenem-resistant Acinetobacter baumannii bacteremia

Abstract: The risk factors for mortality for CRAB included intensive care unit stay, a high Acute Physiology and Chronic Health Evaluation II score, respiratory tract as the origin of bacteremia, and previous use of ceftriaxone. Early implementation of an antimicrobial agent that had the highest in vitro activity against CRAB in patients at risk of CRAB bacteremia and high mortality may improve their outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…In concordance with previous reports (Esterly et al, 2011; Chopra et al, 2013, 2014; Nutman et al, 2014; Fu et al, 2015; Gulen et al, 2015; Gu et al, 2016; Guo et al, 2016; Liu et al, 2016), we found that patients with compromised baseline mobility who are barely capable of carrying any life activities as by their ECOG, with longer hospital stay especially in the critical care units, with ≥1 mg/kg/day of steroids and antimicrobial exposure are at risk for AB bacteremia with poor outcome.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In concordance with previous reports (Esterly et al, 2011; Chopra et al, 2013, 2014; Nutman et al, 2014; Fu et al, 2015; Gulen et al, 2015; Gu et al, 2016; Guo et al, 2016; Liu et al, 2016), we found that patients with compromised baseline mobility who are barely capable of carrying any life activities as by their ECOG, with longer hospital stay especially in the critical care units, with ≥1 mg/kg/day of steroids and antimicrobial exposure are at risk for AB bacteremia with poor outcome.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have demonstrated that crude mortality rates in patients with AB bacteremia varied between 30 and 76%, and factors associated with worse prognosis include immunosuppression (Gulen et al, 2015; Townsend et al, 2015; Gu et al, 2016), drug resistance (Lee et al, 2007; Sunenshine et al, 2007; Fu et al, 2015; Guo et al, 2016), severity of underlying illness (Seifert et al, 1995; Chopra et al, 2013, 2014; Nutman et al, 2014), inappropriate antimicrobial therapy (Esterly et al, 2011; Huang et al, 2012; Shorr et al, 2014; Freire et al, 2016), septicemia (Huang et al, 2012; Ñamendys-Silva et al, 2015; Freire et al, 2016), and prior antibiotic exposure (Chopra et al, 2013, 2014; Gu et al, 2016; Liu et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Given that the impact on mortality of VAP is related to its severity [21], the presence of concomitant A . baumannii bacteremia, whose crude mortality in the setting of pneumonia is high [22], can be understood as a key event that warns on severity and invasiveness of the VAP. A previous surgical procedure was more frequent in VAP than in colonized patients, but this feature was not associated to mortality in the whole sample (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have consistently shown that bacteraemia caused by carbapenem-resistant isolates is associated with unacceptably high mortality when compared to bacteraemia caused by carbapenem-sensitive isolates (Kohler et al, 2017;Falagas et al, 2014;Daikos et al, 2014). In a study of mortality risk factors in 182 patients with carbapenem-resistant A. baumannii bacteraemia in Taiwan, the attributable mortality rate was 58% (Liu et al, 2016). In a retrospective observational study of a cohort of 118 patients with A. baumannii bacteraemia in Korea, the 30-day mortality rate was 34.1% and resistance to carbapenems was identified as one of the significant risk factors for mortality (Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%